2019
DOI: 10.1017/s0033291719001351
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of heart rate variability in major depression

Abstract: BackgroundMajor depression (MD) is a risk factor for cardiovascular disease. Reduced heart rate variability (HRV) has been observed in MD. Given the predictive value of HRV for cardiovascular health, reduced HRV might be one physiological factor that mediates this association.MethodsThe purpose of this study was to provide up-to-date random-effects meta-analyses of studies which compare resting-state measures of HRV between unmedicated adults with MD and controls. Database search considered English and German … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
180
8
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(234 citation statements)
references
References 83 publications
11
180
8
5
Order By: Relevance
“…Finally, the lack of consensus regarding the relation between HRV and depression could also be related to specific characteristics of depression such as the melancholic feature (Borrione et al, 2018), suggesting that depression measures could influence this association with regard to the weight of some items. Anyway, a recent meta-analysis has confirmed that unmedicated depressed patients were lower on HRV than controls (Koch et al, 2019). Further, in a non-clinical sample, depression symptoms were higher when HRV was lower (Paniccia et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Finally, the lack of consensus regarding the relation between HRV and depression could also be related to specific characteristics of depression such as the melancholic feature (Borrione et al, 2018), suggesting that depression measures could influence this association with regard to the weight of some items. Anyway, a recent meta-analysis has confirmed that unmedicated depressed patients were lower on HRV than controls (Koch et al, 2019). Further, in a non-clinical sample, depression symptoms were higher when HRV was lower (Paniccia et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Within this framework, repeated findings reporting the high occurrence of autonomic cardiac alterations among individuals with depression have underlined the potential role of the ANS regulation in the pathophysiological mechanisms of depression (e.g., Hartmann et al, 2019). Several studies in this field support the notion that depression is characterized by an altered autonomic activity, with an increased sympathetic and/or a decreased parasympathetic nervous system activity (Gentili et al, 2017;Koch et al, 2019;Patron et al, 2012;Siever and Davis, 1985;Udupa et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Heart rate variability (HRV), that is, spontaneous oscillations of heart rate around its mean value, is determined by the dynamic interaction of the acceleratory sympathetic nervous system and deceleratory parasympathetic nervous system, indicating a healthy and adaptive organism. Despite the fact that deficient cardiac vagal control indexed by HRV is a common finding in major depression [72,73], a recent study concluded that parasympathetic predominance may precede the onset of depression, thus indicating a risk factor for future major depression [74]. Therefore, HRV analysis represents a promising biomarker-a noninvasive window into neurocardiac regulatory inputs in MDD.…”
Section: Role Of Autonomic Nervous System In Depressive Disordermentioning
confidence: 99%